2006
DOI: 10.1037/1099-9809.12.3.477
|View full text |Cite
|
Sign up to set email alerts
|

Asian Americans and racism: When bad things happen to "model minorities."

Abstract: Due to the limited psychological research on Asian Americans' experiences with racism, in the current study the authors examined the relationships between racial socialization, racial identity, and perceptions of racism, with a college-aged sample (N = 254) consisting primarily of Chinese Americans and Filipino Americans. With the use of multiple regression analyses, the results indicated that racial socialization, particularly discussions about race and racism, was positively related to one's perceptions of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
232
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(258 citation statements)
references
References 17 publications
20
232
2
Order By: Relevance
“…Two multiple moderation models were run separately to assess (1) heterosexist discrimination to psychological distress and (2) racist events to psychological distress. Asian American, the RaLES-DLE has demonstrated adequate re liability yielding Cronbach's alpha of .94 (Alvarez et al, 2006). Cronbach's alpha for RaLES-DLE items in the present study was .94 for both frequency of racist-events and race involvement (see Figure 3).…”
Section: Methodsmentioning
confidence: 79%
“…Two multiple moderation models were run separately to assess (1) heterosexist discrimination to psychological distress and (2) racist events to psychological distress. Asian American, the RaLES-DLE has demonstrated adequate re liability yielding Cronbach's alpha of .94 (Alvarez et al, 2006). Cronbach's alpha for RaLES-DLE items in the present study was .94 for both frequency of racist-events and race involvement (see Figure 3).…”
Section: Methodsmentioning
confidence: 79%
“…A number of recent studies show that Asian American students report higher levels of ethnic/race-based peer discrimination than students from other minority groups (Alvarez, Juang, & Liang, 2006;Choi, Meininger, & Roberts, 2006;Fisher et al, 2000;Goto, Gee, & Takeuchi, 2002;Greene et al, 2006;Grossman & Liang, 2008;Kohatsu et al, 2000;Rivas, Hughes, & Way, in press;Rosenbloom & Way, 2004;Way et al, in press). Alvarez and colleagues' (2006) study of Asian American college students found that 98% reported experiencing at least one racial micro-aggression such as being treated rudely in the past year.…”
Section: Peer Discrimination and Harassmentmentioning
confidence: 94%
“…Although we adjusted for measures of perceived discrimination, these items may not have fully captured the extent of discrimination experienced by Asian/Pacific Islanders attending predominantly minority high schools in our sample. For example, Asian American youth and young adults also experience the perception of being a "perpetual foreigner" who pose a threat economically or educationally (Tuan 1998;Alvarez et al 2006). Future research should consider the negative consequences of not only racially motivated discrimination but also anti-immigrant hostility that may increase feelings of social exclusion.…”
Section: Discussionmentioning
confidence: 99%